Status Imunisasi dan Keragaman Konsumsi Makanan Balita Terhadap Kejadian Stunting - Rika Mianna; Rini Harianti (STIKes Hang Tuah Pekanbaru, 2020)
Stunting begins when the fetus is still in the womb and will be seen when the baby is born. The prevalence of stunting will continue to increase until entering the age of 24-59 months. Some factors that influence the incident are immunization status and diversity of food consumption in infants. This study aims to analyze the relationship between immunization status and diversity of toddler food consumption against stunting. This type of research is observational analytic quantitative research with cross-sectional design. Subjects were mothers with children aged 24-59 months in the working area of ​​UPTD Puskesmas Sungai Apit, Siak, totaling 211 people using systematic random sampling. The results showed that there was a significant correlation between toddlers' immunization status and the incidence of stunting (p = 0.006; POR = 95%; CI = 1,357-4,958). Likewise with the diversity of toddler food consumption on the incidence of stunting (p = 0.002; POR = 95%; CI = 1,516-5,571) showed significant results. It was concluded that immunization status and diversity of food consumption contributed to the incidence of stunting in infants. Keywords: Food consumption, immunization status, stunting, toddler